Static vs. dynamic navigation for endodontic microsurgery - A comparative review - Geo T. D; Payal Saxena; Saurabh Gupta (Elsevier, 2022)
Digitalization of operative procedures through three-dimensional (3D) navigation is a remarkable advancement in the field of dentistry which allows both precision and accuracy while treating patients. It is an emerging technology with a wide variety of applications in dentistry. In the field of endodontics, these computer-aided 3D systems are being used for accessing and localizing canals in calcified teeth, removal of fiberglass posts, and in peri-apical surgeries etc.Preservation of important anatomical structures becomes necessary while performing root-end resection or peri-apical surgeries. However, it is clinically difficult to achieve accurate root-end resection due to the limited field of view, inconvenient perspective, and interferential bleeding among other factors. 3D guided endodontics play vital role here. 3D guided endodontics can be achieved in two ways- Static and Dynamic navigation.Due to availability of limited literature, there is a need to review new evidence comparing the effectiveness of both techniques of 3D guided endodontic navigation systems. This review paper describes the comparative evaluation of the effectiveness of static as well as dynamic navigation in the field of endodontic microsurgery.